Manajemen Pendidik dan Tenaga kependidikan di UPT Sekolah Dasar Negeri 179 Gresik - Siti Nur A’isyah; Silvia Dwi Nur Kamalia; Dewi Ismayani Gendra Bawana; Zahrotun Fisabil Jannah; Ayu Wulandari (Jurnal Pendidikan Dasar Islam, 2024)
This study aims to analyze the management of educators and education personnel at UPT Sekolah Dasar Negeri (SDN) 169 Gresik, with a focus on the management process, the influencing factors, and the outcomes related to enhancing the professional competence of educators. This research employs a descriptive qualitative approach, utilizing data collection techniques such as direct observation, in-depth interviews, documentation, and document analysis. The data were analyzed thematically, following a systematic process of data grouping, data reduction, data presentation, and conclusion drawing. The findings indicate that the management of education personnel at UPT SDN 169 Gresik encompasses several stages: planning, implementation, and evaluation. During the planning stage, a schedule is established, and additional responsibilities are assigned to teaching staff beyond their teaching duties. The implementation stage includes supervising task execution and providing training aimed at improving professional competence. The evaluation stage is conducted periodically through interviews, documentation collection, and performance assessments of teaching staff based on established school management standards. Factors influencing this process include the quality of human resources, school policies, and prioritized student needs. The results of this management approach demonstrate an enhancement in the professional competence of educators, which positively impacts the achievement of educational standards at UPT SDN 169 Gresik. This study concludes that systematic management of educators and education personnel, grounded in student needs, can lead to improved quality of education. The findings may serve as a valuable reference for other educational institutions seeking to manage their teaching staff effectively and efficiently.